Australian and New Zealand Committee on Resuscitation Neonatal Resuscitation guidelines 2016. (2nd July 2017) - Liley, Helen G; Mildenhall, Lindsay; Morley, Peter; ,
Abstract: New Australian and New Zealand Neonatal Resuscitation guidelines reflect recent advances in neonatal resuscitation science, as critically appraised by the International Liaison Committee on Resuscitation. Substantial changes since the 2010 guidelines include: (i) updates to the Newborn Resuscitation Flowchart to include a greater emphasis on maintaining normal body temperature, and to emphasise the importance of beginning assisted ventilation by 1 min in infants who have absent or ineffective spontaneous breathing; (ii) updates to the physiology of the normal perinatal transition that resuscitation is trying to restore; (iii) recommendations for more frequent reinforcement of training, and for structured feedback for resuscitation training instructors; (iv) new guidance in relation to the timing of cord clamping for preterm newborn infants; (v) recommendation to monitor body temperature on admission to newborn units as a resuscitation quality indicator; (vi) suggestion to consider electrocardiographic (ECG) monitoring (as an adjunct to oximetry) to obtain more rapid and accurate estimation of heart rate during resuscitation; (vii) removal of previous suggestions to intubate meconium‐exposed, non‐vigorous term infants to suction the trachea; and (viii) suggestion to establish vascular access to enable administration of intravenous adrenaline (epinephrine) as soon as chest compressions are deemed to be needed.